PEREMPUAN PEMIMPIN DI GEREJA ISA ALMASIH: TINJAUAN DARI PERSPEKTIF TEOLOGI FEMINIS DAN RENEWAL THEOLOGY - Minggus Minarto Pranoto (Sekolah Tinggi Theologia Abdiel, 2018)
This article discusses “Woman as Leader in the Church of Isa Almasih (Christ Jesus)” from the perspective of Feminist Theology and Renewal theology. The writer tries to find the convergence and divergence points of both perspective above, including its method and interpretation in observing the theological basis about the woman as leader. The binder of the big theme to discuss this article from both perspective is the Holy Spirit as the Giver of freedom and equality. From this perspective, the writer tries to make a new proposal about how to give theological inputs to remodel gender stereotype in the context of the Church.